L2 Learners Do Not Ignore Verb’s Subcategorization Information in Real-Time Syntactic Processing - Nakamura, Chie; Arai, Manabu; Hirose, Yuki; Flynn, Suzanne (Frontiers in Psychology, 2022)
This study addressed the question of whether L2 learners are able to utilize verb's argument structure information in online structural analysis. Previous L2 research has shown that L2 learners have difficulty in using verb’s intransitive information to guide online syntactic processing. This is true even though L2 learners have grammatical knowledge that is correct and similar to that of native speakers (Juffs, 1998; Nakamura et al., 2019). In the present study, we contrasted three hypotheses, the initial inaccessibility account, the intransitivity overriding account, and the fuzzy subcategorization frame account, to investigate whether L2 learner’s knowledge of intransitive verbs is in fact ignored in L2 online structural analysis. The initial inaccessibility account and the fuzzy subcategorization frame account predicted that L2 learners cannot access intransitivity information in building syntactic structures in any situation. The intransitivity overriding account predicted that intransitivity information is accessed in L2 parsing, but this process is overridden by the strong transitivity preference when a verb is followed by a noun phrase. Importantly, the intransitivity overriding account specifically predicted that L2 learners can use intransitive information in real-time sentence processing when an NP does not appear immediately following a verb. We tested the three accounts in an eye-tracking reading experiment using filler-gap dependency structures. We manipulated verb’s transitivity information and lexically-based plausibility information and tested English native speakers as a control L1 group (N=29) and Japanese-English L2 participants (N=32). The results showed that L2 learners as well as native speakers processed sentences differently depending on the subcategorization information of the verb, and adopted transitive analysis only when the verb was optionally transitive, providing support for the intransitivity overriding. The results further demonstrated that L2 learners had strong expectations for the transitive structure, which is consistent with the view proposed by the hyper-active gap-filling hypothesis (Omaki et al., 2015). In addition, the results showed that the semantic mismatch in the incorrect transitive analysis facilitated native speaker’s processing but caused difficulty for L2 learners. Together, the current study provides evidence that L2 learners use intransitive information of the verbs to guide their structural analysis when there are no overriding constraints.